دنیاوی جاہ و حشمت اور آرزوے بہشت: بنگال کے اسلامی کتبات میں القاب کا تنوع - پروفیسر ڈاکٹر محمد یوسف صدیق (FIKR-O NAZAR فکر ونظر, 2013)
The titles have been a symbol of divergent civilizational and cultural meanings. They have been used for religious and political figures in Islamic history to represent various dimensions of their personalities. Sometimes these titles represent reality and sometimes they exaggerate the qualities of those to whom they are attributed. Bengal was ever very rich and elegant for its monumental inscriptions containing such titles, and we can find them in several historical monuments. This article studies these titles, the places where they are found and the people for whom they have been used.